Violations of Grice`s Maxims in The Prince and the Pauper Movie - Waget, Antonius (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2015)
Proper responses must be provided interlocutors to make onversationproductive and meaningful. However, interlocutors do not always provide properresponses because they do not even know conversation rules. Grice coins 4 maximsas general rules to govern daily conversation. The maxims are Quantity, Quality,Relevance, and Manner. Conversation occurs in the real daily interaction also in artsincluding movies. The Prince and the Pauper movie is one of the media for humandaily conversation. Some parts of the movie contains violations of Grice`s maxims bythe characters. Based on this background, the writer intends to explore violations ofGrices maxims in the movie and analyze the purposes of the violations. To achievethese objectives, the writer formulates two research problems: (1) Which of Grice`smaxims are violated by the addressees in The Prince and the Pauper movie? (2) Forwhat purposes do the addressees violate the maxims? The base of this research is amovie script as document. Thus, the writer uses document analysis as the methodof this research. Grounded on the analysis, the writer finds that the characters, especially Prince, Tom Canty, King, and the Earl of Hertford in the movie dialoguesviolate the four of Grice`s maxims. When failing to provide sufficient information,telling lie to their addressers, providing irrelevant glosses, and failing to be true,brief, univocal, and orderly, they respectively violate maxims of Quantity, Quality,Relevance, and Manner. Moreover, the writer finds that the characters violate themaxims in order to mislead the counterparts, be polite, save face, avoid discussion,and communicate self-interest.